Gait Pattern and Lower Extremity Alignment in Children With Diastrophic Dysplasia. Issue 7 (October 2016) - Bayhan, Ilhan A.; Er, Mehmet S.; Nishnianidze, Tristan; Ditro, Colleen; Rogers, Kenneth J.; Miller, Freeman; Mackenzie, William G.
Abstract : Background: The aim of this study was to describe the dynamic lower extremity alignment in children with diastrophic dysplasia (DD) by 3-dimensional gait analyses. Our main hypothesis was that gait kinematics and kinetics are different than the age-normalized population and patellar dislocation can alter the gait in patients with DD. Methods: A retrospective review of clinical data and radiographs was conducted for patients with DD who had gait analysis before lower extremity skeletal surgery excluding foot procedures. Lower extremity range of motion was measured. The Pediatric Outcomes Data Collection Instrument (PODCI) was administered to parents to evaluate their children's functional status. Gait laboratory data were collected to compare the hip and knee kinematics in cases with and without patellar dislocation. Anteroposterior standing radiographs were taken for all patients to assess the correlation between measurements (clinical, radiologic, and gait) for coronal knee alignment. Results: Thirty lower extremities of 15 children (7 females and 8 males) were evaluated. The mean age was 7.4±3 years, the mean height was 97.7±15 cm ( z =−5.1), and the mean weight was 20.6±6.2 kg ( z =−0.8). The DD PODCI subscores were statistically significantly lower ( P <0.05) than the average stature for developing children, except for the happiness score. Gait analysis, compared between all DD and an age-normalized average stature group, showed decreased forward velocity, step length, and stride length with an increased average forward tilt of the trunk and pelvis, hip flexion, hip adduction, and internal rotation ( P <0.001). Delta hip and knee motion were also decreased ( P <0.001). The patella was dislocated in 19 (63.3%) and central in 11 (36.6%) knees. Comparison of the minimum knee and hip flexion at the stance phase demonstrated increased crouch gait in the patellar dislocation group ( P <0.001). Knee alignment measurements between clinical examination and gait analysis showed moderate correlation ( r, 0.476; P =0.008). Conclusions: Children with DD demonstrated lower PODCI subscores except for happiness. Gait analysis showed limited lower extremity function of the children with DD in our study group. Patella dislocation group had increased crouch gait. Levels of Evidence: Level III—diagnostic study.